Russia-Nato relations: Stagnation or revitalization? - Hannes Adomeit; Frank Kupferschmidt (Stiftung Wissenschaft und Politik (SWP), 2008)
For more than a decade, Nato has made efforts to achieve a "qualitatively new" relationship with Russia based on mutual trust and understanding. Practical cooperation and the broadening of contacts and exchanges were to have been the means to achieve these ends. Initially, this was held to be a realistic goal. Today, however, disappointment and frustration prevail in the Atlantic alliance. Moscow, in turn, has done little to encourage less pessimistic perceptions.Against this background, the research paper analyzes the reasons why the high expectations, extant in particular after the terror attacks of September 11, 2001, and the foundation of the new Nato-Russia Council in May, 2002, failed to materialize. In its main part, the paper examines areas of cooperation and conflict, as well as assets and liabilities, and provides a balance sheet of the relationship. It furthermore deals with the question as to the determinants and motive forces responsible for the fact that on the balance sheet the liabilities are more pronounced than the assets and that a major part of the cooperation has been symbolic rather than substantive. Nevertheless, whereas Russia may not have become a "strategic partner" of the Alliance, it also has not returned to being an adversary. Assets have been built up in the form of cooperative structures that can be utilized to revitalize the relationship once more favorable external conditions obtain.Based on this assumption, the paper deals with options for German and European policy. It advocates utilization of the cooperative potential that has accumulated but argues that the martial rhetoric in evidence at present in Moscow should be met with equanimity. The Nato-Russia Council should be used more extensively as a forum of discussion, and new areas of cooperation should be explored
Keywords: 320; Russische Föderation